(untitled) (ItalianoLinguadue, 2023)
The Italy of mobility: ancient confirmations and unexpected discoveries What happened to Italian mobility in the last 17 years? The only Italians who have been growing are those who put down roots abroad, leaving their country in the grasp of decreased birth-rate and depopulation. The pandemic emergency has not stopped the departures. Today, after almost three years of healthcare emergency and with a one-year war in the heart of Europe, did our fellow countrymen stop the departures abroad? Did they change their destinations? Starting with the new edition of the Rapporto Italiani nel Mondo (2022) of Fondazione Migrantes and travelling again through the history of this cultural project, this article describes the phenomenon of our Italy experiencing an endless mobility with continuous changing characteristics. The analysis will focus both on today’s mobility, which recalls the emigration of the past, and on some unexpected news.